INVESTIGATING FACTORS THAT AFFECT THE CONTINUANCE USE INTENTION AMONG THE HIGHER EDUCATION INSTITUTIONS’ LEARNERS TOWARDS A GAMIFIED M-LEARNING APPLICATION - Roslan, Rosfuzah; Mohd Ayub, Ahmad Fauzi; Ghazali, Norliza; Zulkifli, Nurul Nadwa; Md Latip, Siti Noor Haslina; Abu Hanifah, Siti Syuhada
The main purpose of this study is to identify the factors affecting the continuance use intention of gamified m-learning applications by Higher Education Institution (HEI) learners in Malaysia.